2012
DOI: 10.1016/j.amepre.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician Interventions and Thirdhand Smoke Beliefs of Parents

Abstract: Background Thirdhand smoke is residual tobacco smoke contamination that remains after a cigarette is extinguished. A national study indicates that adults’ belief that thirdhand smoke (THS) harms children is associated with strict household no-smoking policies. The question of whether pediatricians can influence THS beliefs has not been assessed. Purpose To identify prevalence of THS beliefs and associated factors among smoking parents, and the association of pediatrician intervention on parent belief that TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 9 publications
1
35
2
4
Order By: Relevance
“…Although there is a general public awareness about the harms of SHS, the general public are more sceptical about THS, with a study in 2009 finding that 62.5% of non-smokers and 43% of smokers agreed that THS harms children (Winickoff et al, 2009). A study of parents' attitudes found that fathers and heavy smokers (N10 cigarettes per day) were less likely to believe that THS was harmful (Drehmer et al, 2012). The specific role of THS in tobacco-related illnesses has been questioned by the public health community (Matt et al, 2011a), however, a recent study demonstrated that chemical species associated with THS are genotoxic in human cell lines (Hang et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Although there is a general public awareness about the harms of SHS, the general public are more sceptical about THS, with a study in 2009 finding that 62.5% of non-smokers and 43% of smokers agreed that THS harms children (Winickoff et al, 2009). A study of parents' attitudes found that fathers and heavy smokers (N10 cigarettes per day) were less likely to believe that THS was harmful (Drehmer et al, 2012). The specific role of THS in tobacco-related illnesses has been questioned by the public health community (Matt et al, 2011a), however, a recent study demonstrated that chemical species associated with THS are genotoxic in human cell lines (Hang et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Sigara içen anne ve babalar üzerinde yapılan bir ça-lışmada ailelerin bu etkiyi önemsemedikleri ve hatta inanmadıkları gözlenmiştir (22) . Bu nedenle gerek yöneticilerin, gerek sağlık çalışanlarının bu noktaya dikkatini çekmek için toplumsal çalışmalar yapılmalı-dır.…”
Section: Pasif İçicilik Ve Thirdhand Smokeunclassified
“…10,[12][13][14][15][16][17] In brief, all parents of children making any type of visit were approached immediately after the visit by an RA and asked to be interviewed. Those who spoke English, had smoked a cigarette (even a puff) within the past 7 days, were aged 18 years or older, and would have a contact number to be reached over the next year were eligible for enrollment.…”
Section: Methodsmentioning
confidence: 99%